Reducing the Incidence of Nosocomially Affected Infections - Dobnik, Mojca; Lorber, Mateja (45th International Conference on Organizational Science Development: Organization and the Longevity Society, Conference Proceedings, 2026)
Hospital infections in Slovenia constitute a growing problem in the field of quality and safety for both patients and employees, and consequently for the associated costs. The incidence of hospital infections is also related to patient isolation, and other measures to prevent the transmission of infection. At a tertiary institution, we performed 934 disinfections over 1 year using a modern device. In one of the departments, we conducted a comparative analysis of disinfection procedures performed before cleaning, after manual cleaning and disinfection, and after the use of modern devices. We observed substantial growth of multidrug-resistant bacteria before cleaning; poor growth in four cases; and strong growth in one case after manual cleaning and disinfection. After using a modern device, no growth of multidrug-resistant bacteria was detected. When it comes to the cost of hospital infections and their prevalence, management faces an important question: Is the purchase of modern equipment a cost or an investment? We can conclude that this is an investment, including in the provision of high-quality, safe healthcare for patients and employees.